2018
DOI: 10.1002/nau.23744
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lower urinary tract symptoms on work productivity in female workers: A systematic review and meta‐analysis

Abstract: Evidence suggests that female workers with LUTS had significantly greater work productivity impairment compared to those without LUTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 45 publications
(153 reference statements)
0
21
0
Order By: Relevance
“…According to a global survey, 423 million people had symptoms of urinary incontinence in 2018 (Griebling, 2011). Urinary incontinence is often accompanied by lower work productivity and movement disorders (Lin, Siu, & Lin, 2018), which increases the risk for developing major depression and mortality (Bogner et al, 2002; Chen et al, 2010; Damián, Pastor‐Barriuso, García López, & de Pedro‐Cuesta, 2017; Gambassi et al, 1999; Luk et al, 2013). Cheng et al reported that patients with urinary incontinence had a 1.59‐fold risk for depression in comparison with those without urinary incontinence (Cheng et al, 2020).…”
mentioning
confidence: 99%
“…According to a global survey, 423 million people had symptoms of urinary incontinence in 2018 (Griebling, 2011). Urinary incontinence is often accompanied by lower work productivity and movement disorders (Lin, Siu, & Lin, 2018), which increases the risk for developing major depression and mortality (Bogner et al, 2002; Chen et al, 2010; Damián, Pastor‐Barriuso, García López, & de Pedro‐Cuesta, 2017; Gambassi et al, 1999; Luk et al, 2013). Cheng et al reported that patients with urinary incontinence had a 1.59‐fold risk for depression in comparison with those without urinary incontinence (Cheng et al, 2020).…”
mentioning
confidence: 99%
“…Fourteen patients (14/59, 23.7%) including 3 who had prior DO, experienced persistent improvement of symptoms after a median number of injections of 2 [1][2][3][4][5] and did not require any reinjections. Of them, 8 received 250 U, 5 had a higher dosage (500 U) and one was switched to onabotulinumtoxinA 100 U after first injection.…”
Section: Causes Of Discontinuationmentioning
confidence: 99%
“…Overactive bladder (OAB) is defined as the presence of urinary urgency usually associated with frequency and nocturia, with or without urgency urinary incontinence [1]. Idiopathic overactive bladder (iOAB) is highly prevalent and greatly impacts health related quality of life (HRQOL) and work productivity [2][3][4]. When conservative measures and medical treatment have failed, intra-detrusor injections of botulinum toxin A (BoNT-A) can be proposed as a second line treatment [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While urinary symptoms can compromise the quality of life and productivity 5 , urinary tract infections are associated with high antibiotic prescriptions 6 and an increased risk of antibiotic-resistant urinary pathogens 7 .…”
Section: Introductionmentioning
confidence: 99%